O processo regulatório da educação superior a distância no Brasil - Marcio Mugnol (EccoS – Revista Científica)
This article analyzes the implementation of distance education in higher education from the development of their legal frameworks in Brazil. We intend to show that the initial position of the MEC, under the management of Paulo Renato minister, was virtually indiscriminate opening of the federal system of higher education for the operation of the distance mode by the private sector. This policy was mainly being revised from 2007, already in Fernando Haddad management with the creation of a new institutional framework for both the supervision and for evaluation of institutions and courses.